MORAL PAJAK: SEBUAH OPSI PENINGKATAN KEPATUHAN PAJAK MASYARAKAT MUSLIM - Pertiwi, Imanda Firmantyas Putri (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2017)
This study aims to determine the significance of taxpayer internal factors to comply with applicable tax laws. Variable religiosity and nationalism become exogenous variables to define tax morale, while tax morale will define tax compliance. Samples taken over 200 individual taxpayers whose Islam religion. Data analysis was done using Structural Equation Model (SEM) by dividing the step into outer test and inner test. The results showed that statistically religiosity influence tax morale, but on the contrary, nationalism is not shown significant results. Tax morale on tax compliance showed positive results and significant. Based on these results, can be concluded that religiosity still plays an important role in moslem society